8-(-10)=-12-3p

Simple and best practice solution for 8-(-10)=-12-3p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8-(-10)=-12-3p equation:


Simplifying
8 + -1(-10) = -12 + -3p

Multiply -1 * -10
8 + 10 = -12 + -3p

Combine like terms: 8 + 10 = 18
18 = -12 + -3p

Solving
18 = -12 + -3p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '3p' to each side of the equation.
18 + 3p = -12 + -3p + 3p

Combine like terms: -3p + 3p = 0
18 + 3p = -12 + 0
18 + 3p = -12

Add '-18' to each side of the equation.
18 + -18 + 3p = -12 + -18

Combine like terms: 18 + -18 = 0
0 + 3p = -12 + -18
3p = -12 + -18

Combine like terms: -12 + -18 = -30
3p = -30

Divide each side by '3'.
p = -10

Simplifying
p = -10

See similar equations:

| 16-14x=-5(7x+3)-5(-4-4x) | | 7-5t=nfort | | y=-4(4)+4 | | 108=96x-16x^2 | | h^2=144 | | 8x6/10 | | 22-13=3(x-5) | | y=-4(-1)+4 | | 5*5*5+6(2-17)-(-4)= | | y+10+2y+5=180 | | 140=2x+20+x^2 | | (-2)=(-9) | | -3x+9-3x=39 | | x4/3+3x4/3-28=0 | | -5/6+c=11/12 | | 8=-4x+4 | | 6-2(y+5)=-5 | | =14x+5 | | -5c+4=-6 | | -1/8x-3/4 | | x-2(-5)=10 | | 1.6y-3.5=6.4-1.7 | | 6p-12+8p=5p-20-10 | | 9/5(43)+32 | | x(x-8)=x | | 2x^2+3x=30 | | x-2(-4)=10 | | 1/2(3x+2)-1/2(x+6)=5 | | f=9/5*43+32 | | y-16/2+y-9/7=-8 | | =x+15 | | 15=7.5+2.5y |

Equations solver categories